Regularities of structural-cellular structure of ovaries in ontogenesis - E. V. Timofeyeva; Y. A. Vysotskiy; G. N. Borodina; S. V. Lopatina (Acta Biomedica Scientifica, 2016)
The article presents the examination of the ovaries of embryos, ovaries of human feti and ovaries of children of the tender age. The researches revealed the increase of the surface of follicles, nucleus and primary oocyte's cytoplasm that tells about the fact that further follicular maturation continues in the ovaries of a child of 2-4 months old. Also we registered the increase of nuclear cytoplasmic ratio, appearance of single mature follicles with cumulus oophorus that testifies to the fact that the ovary is functionally mature. Furthermore the research revealed increased content of lipids and DNA in follicular epithelium that also tells aboutfunctional maturity of the ovary. It was found that incretory activity of an ovary during the first year of life is provided by the cells originated from the connective tissue membrane of atresic follicles.